Kinetic modeling of the sesamin conversion into asarinin in the presence of citric acid loading on Hβ - Yu, Qiong; Cai, Xiao-shuang; Leveneur, Sébastien; Wang, Xue-de; Liu, Hua-min; Zhang, Chen-xia; Ma, Yu-xiang (Frontiers in Nutrition, 2022)
In the present work, effects of reaction temperature, reactant concentration, catalyst loading and rotation speed on the kinetics of sesamin conversion in a sesame oil system were studied by using citric acid loading on Hβ zeolite (CA/Hβ) as a catalyst. A kinetic model was built for sesamin conversion. The kinetic model fits correctly the experimental concentration of seasmin and asarinin (R_Sesamin^2=0.93 and R_Asarinin^2=0.97). The sesamin conversion is an endothermic reaction (∆H_(r Iso)=34.578 kJ/mol). The CA/Hβ catalyst could be easily regenerated by calcination, and there was no obvious loss of catalytic activity when reused. Knowledge of the sesamin conversion is of great significance for guiding production and improving the value and nutrition of sesame oil. In a word, this study lays the foundation for the scale-up of the production of asarinin from sesame oil using CA/Hβ as the catalyst.